2021
DOI: 10.1021/acsami.1c17700
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Template-Derived Multielectron Reaction NASICON Structure Na3MnTi(PO4)3 for High-Performance Sodium-Ion Batteries

Abstract: The sodium super ion conductor (NASICON) structure materials are essential for sodium-ion batteries (SIBs) due to their robust crystal structure, excellent ionic conductivity, and flexibility to regulate element and valence. However, the poor electronic conductivity and inferior energy density caused by the nature of these materials have always been obstacles to commercialization. Herein, using yeast as a template to derive NASICON structure Na 3 MnTi(PO 4 ) 3 (NMTP) materials (noted as Yeast@NMTP/C) is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 60 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…These results above were accordant to previous reports for Na 3 MnTi(PO 4 ) 3 . [ 22 ] The XPS analysis was implemented to detect the surface elemental composition and valence states of two samples. In the high‐resolution Mn 2p spectrum (Figure S3a, Supporting Information), the sharp peaks centered at 653.9 and 642 eV represent the electrons of Mn 2p 1/2 and Mn 2p 3/2 , which are characteristic of Mn 2+ species for M 1.2 T 0.8 material.…”
Section: Resultsmentioning
confidence: 99%
“…These results above were accordant to previous reports for Na 3 MnTi(PO 4 ) 3 . [ 22 ] The XPS analysis was implemented to detect the surface elemental composition and valence states of two samples. In the high‐resolution Mn 2p spectrum (Figure S3a, Supporting Information), the sharp peaks centered at 653.9 and 642 eV represent the electrons of Mn 2p 1/2 and Mn 2p 3/2 , which are characteristic of Mn 2+ species for M 1.2 T 0.8 material.…”
Section: Resultsmentioning
confidence: 99%
“…Optimizing the morphology and architecture is also critical for improving the electrochemical properties of LTMOs. [126,127] Furthermore, nanostructures have been widely utilized to enhance electrochemical performance through enhanced redox reactions, reduced ionic transport channels, and relief of lattice strain. [128] For example, Liu et al reported the preparation of hollow P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 nanofibers constructed from nanoparticles via electrospinning.…”
Section: Structural Designmentioning
confidence: 99%
“…Also, yeast cells contain a large number of polar groups, such as hydroxyl and carboxyl, which have a strong ability to adsorb ions and enter the cell by ion concentration diffusion and active transport. During the sol-gel process, the raw materials were immobilized on the surface and inside of yeast cells, and finally, nanoscale NVP crystals were obtained during the sintering process [62,79,80]. Zhu et al successfully synthesized NVP nanoparticles (NVP@C) using yeast cells, and the synthesis process is shown in figure 3(a) [62].…”
Section: Nvp Nanoparticles and Nvp With 0d Carbon Materialsmentioning
confidence: 99%